VALUING PUBLIC TRANSPORTATION USING CONTINGENT VALUATION METHOD: A STUDY OF COMMUTER LINE (KRL) IN TANGERANG SELATAN, WEST JAVA INDONESIA - Saptutyningsih, Endah; Karimah, Laila (Jurnal Ekonomi & Studi Pembangunan, 2019)
This study aims to find out how much the Commuter Line (KRL) users’ willingness to pay (WTP) for improving the quality of train service and identify the determinants of Commuter line (KRL) users’ WTP for improving the quality of train service. The method used in this study is the contingent valuation method (CVM). The data were collected by face to face interviews with users of the Electric Rail Train. The results of this study show that the average WTP for improving the quality of KRL services is IDR 4,500. The cleanliness, comfort, travel time, and income of KRL users affect the WTP users to improve the quality of KRL services. This study is expected to improve the quality of KRL services, especially in South Tangerang, and can be a reference for managers for public transportation services.